2004
DOI: 10.1038/sj.bjp.0705599
|View full text |Cite
|
Sign up to set email alerts
|

Desensitisation of mast cell β2‐adrenoceptor‐mediated responses by salmeterol and formoterol

Abstract: 1 The long-acting b 2 -adrenoceptor agonist formoterol (10 À10 -10 À6 M) inhibited the IgE-dependent release of histamine from human lung mast cells in a concentration-dependent manner. Formoterol was more potent and a full agonist relative to the nonselective b-adrenoceptor agonist isoprenaline. By contrast, the long-acting b 2 -adrenoceptor agonist salmeterol (10 À10 -10 À6 M) was about two-thirds less efficacious than either formoterol or isoprenaline as an inhibitor of histamine release. 2 Isoprenaline, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
2
43
1
2
Order By: Relevance
“…This concurs with studies examining the effects of these b 2 -agonists on histamine release from mast cells and mediator release from eosinophils [33] where salmeterol is less efficacious than formoterol [34]. The data presented in this study differ from that observed in THP-1 cells that were differentiated towards a macrophage phenotype with phorbol myristate acetate, where neither formoterol nor salmeterol inhibit LPS-stimulated TNF-a release [14].…”
Section: Cell and Animal Studies Le Donnelly Et Alcontrasting
confidence: 56%
“…This concurs with studies examining the effects of these b 2 -agonists on histamine release from mast cells and mediator release from eosinophils [33] where salmeterol is less efficacious than formoterol [34]. The data presented in this study differ from that observed in THP-1 cells that were differentiated towards a macrophage phenotype with phorbol myristate acetate, where neither formoterol nor salmeterol inhibit LPS-stimulated TNF-a release [14].…”
Section: Cell and Animal Studies Le Donnelly Et Alcontrasting
confidence: 56%
“…Previously, it was shown that the inhibitory effects were associated with the affinity to the β 2 -receptor (15). Formoterol was demonstrated to have a more efficient effect on stabilizing the mast cell membranes than salmeterol as it had a higher affinity to the receptor (15). In the present study, the role of SPFF and its enantiomers in stabilizing mast cells was investigated by determination of the release of inflammatory mediators from the lungs of allergic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the fast phase, β 2 agonists exerted inhibitory effects on the mediators released from mast cells and the degranulation of the cells (14). Previously, it was shown that the inhibitory effects were associated with the affinity to the β 2 -receptor (15). Formoterol was demonstrated to have a more efficient effect on stabilizing the mast cell membranes than salmeterol as it had a higher affinity to the receptor (15).…”
Section: Discussionmentioning
confidence: 99%
“…11,13,[31][32][33] The increase in sputum inflammatory cells 31,34 after regular use of beta2-agonists suggests they could paradoxically have a proinflammatory effect. Regular exposure to LABAs can cause functional desensitization of the 35 and airway smooth muscle. 36 The complex signaling pathway underlying the relationship between AHR and the β2AR is still being explored.…”
Section: Fraction Of Exhaled Nitric Oxidementioning
confidence: 99%
“…11,13,[31][32][33] The increase in sputum inflammatory cells 31,34 after regular use of beta2-agonists suggests they could paradoxically have a proinflammatory effect. Regular exposure to LABAs can cause functional desensitization of the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 35 and airway smooth muscle.…”
mentioning
confidence: 99%